Principles of corporate governance with specific reference to the case of South African Broadcasting Corporation (LTD) V Mpofu [2009] 4 all SA 169. (GSJ) - Sebola, Kgabo Reginald (My University, 2012)
This mini-dissertation highlights corporate governance initiatives in South Africa, focusing on the proposed governance reforms. An analysis of the major corporate governance reform is done including, statutory reforms, development of codes of conduct and practice and institutional reforms. The evolution of South Africa’s corporate structure and forces driving corporate governance is examined. It is noted that corporation in South Africa cannot shield themselves from the global movement shaping the standard principle governing corporations. Therefore the global principle corporate governance are examined concerning how they can serve as models for enhancing corporate governance standard in South Africa. The analysis is based on the need to bring South Africa’s corporate governance in line with international accepted standard but considering the best interest of South Africa and its citizen.
Thesis (LLM. (Development and management law)) -- University of Limpopo, 2012
Keywords: Corporate governance; Company law; Corporate governance -- Law and legislation -- South Africa; Corporate governance; Corporation Law -- South Africa -- Cases